2011
DOI: 10.1089/jwh.2010.2476
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Vaginal Film, Soft-Gel Capsule, and Tablet as Potential Microbicide Delivery Methods Among African Women

Abstract: All three dosage forms were acceptable to the women surveyed. Preferred dosage forms varied by country. These data suggest that the availability of microbicides in multiple dosage forms may increase acceptability, adherence, and, therefore, effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 15 publications
2
56
0
1
Order By: Relevance
“…Second, rapid hydration rates of fibers may minimize the risk of epithelial abrasions caused by the intravaginal dosage form if applied immediately before sex. The observation that fibers transform into a semisolid with gellike properties could prevent the sensation of "dry" sex often attributed to dry-dose microbicides (31). Also, since high-M w polymers (M w Ͼ 100 kDa) are utilized for electrospinning, the osmolality of dissolved fibers may be significantly lower than that of dissolved films incorporating lower-M w polymers (polyvinyl alcohol with M w of ϳ10 kDa) and excipients like PEG 400 and glycerol (ϳ10 to 100 times lower moles of solute per volume in fibers than in films).…”
Section: Discussionmentioning
confidence: 99%
“…Second, rapid hydration rates of fibers may minimize the risk of epithelial abrasions caused by the intravaginal dosage form if applied immediately before sex. The observation that fibers transform into a semisolid with gellike properties could prevent the sensation of "dry" sex often attributed to dry-dose microbicides (31). Also, since high-M w polymers (M w Ͼ 100 kDa) are utilized for electrospinning, the osmolality of dissolved fibers may be significantly lower than that of dissolved films incorporating lower-M w polymers (polyvinyl alcohol with M w of ϳ10 kDa) and excipients like PEG 400 and glycerol (ϳ10 to 100 times lower moles of solute per volume in fibers than in films).…”
Section: Discussionmentioning
confidence: 99%
“…The film is folded once, placed over the dry finger and inserted high into the vagina. Besides, they offer various other advantages that include ease in use, no messiness, comfort, unimpeded sexual activity and reduced cost (34). The major components employed to develop vaginal films include active pharmaceutical ingredient (API), polymers that form water soluble film and plasticizers to increase elasticity (35).…”
Section: Vaginal Filmsmentioning
confidence: 99%
“…The success with oral TDF and Truvada, TDF in combination with emtricitabine (FTC), in inhibiting HIV infection in nonhuman primates led to the clinical trials in humans with TDF and Truvada (1, 6-11). In stark contrast to the success of TDF and Truvada in clinical trials in men who have sex with men and heterosexual HIV-discordant couples, two large clinical trials in women with oral Truvada, VOICE and FEM-PrEP, have demonstrated no protection due to a lack of adherence (12, 13).Providing optimal dosage forms of potent HIV PrEP agents for women has the potential to improve product adherence (14,15). Topical dosage forms can be effective in reducing HIV infection, as demonstrated by the CAPRISA 004 vaginal 1% tenofovir (TFV) gel trial, where per-protocol use of the gel before and after sex with no more than 2 doses in 24 h (BAT-24) reduced HIV acquisition by 39% (2).…”
mentioning
confidence: 99%
“…Providing optimal dosage forms of potent HIV PrEP agents for women has the potential to improve product adherence (14,15). Topical dosage forms can be effective in reducing HIV infection, as demonstrated by the CAPRISA 004 vaginal 1% tenofovir (TFV) gel trial, where per-protocol use of the gel before and after sex with no more than 2 doses in 24 h (BAT-24) reduced HIV acquisition by 39% (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation